Migration, Education and the Gender Gap in Labour Force Participation - Ilhom Abdulloev; Ira Gang; Myeong-Su Yun (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Women who want to work often face many more hurdles than men. This is true in Tajikistan where there is a large gender gap in labour force participation. We highlight the role of two factors - international migration and education - on the labour force participation decision and its gender gap. Using probit and decomposition analysis, our investigation shows that education and migration have a significant association with the gender gap in labour force participation in Tajikistan. International emigration from Tajikistan, in which approximately 93.5% of the participants are men, reduces labour force participation by men domestically; increased female education, especially at the university and vocational level, increases female participation. Both women acquiring greater access to education and men increasing their migration abroad contribute to reducing the gender gap.
Keywords: J01; J16; O15; 330; migration; education; gender gap; labour force participation; Tajikistan